Implantable cardiac defibrillators for patients with non‐ischaemic cardiomyopathy - El Moheb, Mohamad (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To evaluate the effects of implantable cardiac defibrillators on patients with non‐ischaemic cardiomyopathy compared to optimal medical therapy, and the adverse events associated with using these devices.